The Effectiveness of E-Trilingua Dictionary Learning Media to Improve the Vocabulary of Students with Special Needs at Baiturrahman Special Needs School, Bima - Nurnaningsih, Nurnaningsih; Muslimin, Ikhwannul; Ramli, Ramli (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Vocabulary mastery is one of the fundamental aspects in language skills, especially for students with special needs (SBK) who have limitataions in accesing information verbally. This study aims to analyze the effectiveness of the ETilingua Dictionary leraning media. a Trilingua-based electronic dictionary (Bima-Indoensia-English) in improving students’ vocabulary at Baiturrahman Bima as a special need school. Penelitian menggunakan metode deskriptif kualitatif dan kuantitatif sederhana melalui observasi, wawancara, serta tes pre-test dan post-test. Hasil data menunjukkan rata-rata peningkatan nilai vocabulary dari 48% pada pre-test menjadi 82% pada post-test, dengan kategori peningkatan tinggi (N-Gain = 0.65).This increae proves that the E-Trilingua dictionary is effective in improving vocabulary mastery of students with special needsa at Baiturrahman Bima special needs school. The implication is that the interactive E-trilingua Dictionary media is suitable to be used as medium into language leanring at SLB.